Protection of Rights of Women Labour Force as Development Actors in Indonesia - Yunita, Primadiana; Hadi, Rany Purnama (Universitas Muhammadiyah Malang, 2022)
This paper examines the current trajectory of Indonesian Government in protecting the rights of female labour force. The World Bank data shows that female labour participation rate in Indonesia has been rising form 38% in 2015 to 39.3% in 2020. Women has indeed make an essential contributions to economic development in all developing countries. Their roles vary considerably between and within regions and are changing rapidly in many parts of the world, where economic and social forces are transforming the agricultural sector to industrial sector. However this positive outcome is sometimes does not followed by the equal protection of rights toward female labour in Indonesia. Invariably women are over represented in unpaid, seasonal and part-time work, and the available evidence suggests that women are often paid less than men, for the same work. This study employs qualitative and descriptive methods with comprehensive analysis. It will also apply combination of primary and secondary data that will be collected from every sources particularly government official publication. Using the concept of Gender and Development (GAD), the aims of this research is to analyse the current condition of female labour force participation in Indonesia, and also how the Government attempt to protect the rights of female labour as one of the main actor in Indonesia’s economic development from gender point of view. Our projection shows that the Indonesia Government current policy still was not able to provide protection toward female labour force’s rights despite its rising in participation rate.Key words: Gender, Development, Economics, Indonesia, Female Labour Force